2004
DOI: 10.1152/ajpheart.00364.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical compression elicits NO-dependent increases in coronary flow

Abstract: Our previous studies have demonstrated that a decrease in arteriolar diameter that causes endothelial deformation elicits the release of nitric oxide (NO). Thus we hypothesized that cardiac contraction, via deformation of coronary vessels, elicits the release of NO and increases in coronary flow. Coronary flow was measured at a constant perfusion pressure of 80 mmHg in Langendorff preparations of rat hearts. Hearts were placed in a sealed chamber surrounded with perfusion solution. The chamber pressure could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…An increase in guanylate cyclase activity, indicating an increase in NO release, was demonstrated in the effluent from rhythmically compressed femoral artery rings (LaMontagne et al 1992). In coronary arterioles, dilatation in response to longer periods of constant extravascular pressure (20-60 s) was NO dependent (Sun et al 2004). To our knowledge, there have been no previous studies examining vascular deformation and the release of prostaglandins or endothelium-derived hyperpolarizing factor.…”
Section: Discussionmentioning
confidence: 93%
“…An increase in guanylate cyclase activity, indicating an increase in NO release, was demonstrated in the effluent from rhythmically compressed femoral artery rings (LaMontagne et al 1992). In coronary arterioles, dilatation in response to longer periods of constant extravascular pressure (20-60 s) was NO dependent (Sun et al 2004). To our knowledge, there have been no previous studies examining vascular deformation and the release of prostaglandins or endothelium-derived hyperpolarizing factor.…”
Section: Discussionmentioning
confidence: 93%
“…The mechanism by which the increase in smooth muscle [Ca 2ϩ ] i leads to increase in endothelial [Ca 2ϩ ] i is not addressed in the present study. Myoendothelial coupling in afferent arterioles may allow diffusion of Ca 2ϩ or IP 3 through gap junction (3,14,25,26), and release of extracellular messengers may occur or opening of mechanosensitive endothelial cation channels may be initiated by the vasoconstriction (8,20,(22)(23)(24)32). The latter mechanism may provide one explanation of why calcium is transferred from smooth muscle to endothelium during vasoconstriction, while an increase in endothelial [Ca 2ϩ ] i induced by acetylcholine was not transferred to the smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, they suggested that a vasoconstrictor-mediated increase in smooth muscle [Ca 2ϩ ] i is transferred to the endothelial cells where it activates endothelial NO synthase and enhances formation of NO, which diffuses back to the smooth muscle and reduces/buffers contraction. On the other hand, deformation of the endothelium during vasoconstriction and consequent release of NO have also been described (22,23).…”
mentioning
confidence: 99%
“…(2006) has demonstrated that pulse pressure eliciting mechanical deformation of isolated rat soleus feed arteries can significantly increase vasodilation, which was partly mediated by the vascular endothelium. Thus, it is uncertain in the present study whether the fast contraction velocity stimulated a greater release of vasoactive substances than the slow contraction velocity through the mechanical strain of the vessel wall associated with muscle contractions (Sun et al. , 2004) or by the haemodynamic shear stress produced by rhythmic exercise.…”
Section: Discussionmentioning
confidence: 80%